Новi риси нанонауки у порiвняннi з фiзикою i хiмiєю - Osawa, E. (Publishing house "Academperiodika", 2019)
A few novel observations that we encountered while practicing nanoscience are analyzed and interpreted. Topics taken up here include the invalidation of purity supremacy; concentration dispersion, dilution aggregation; importance of modeling; quantization; and number density effect. Contrary to the general belief that nanoscience has its own advantages and disadvantages, we find that all of the peculiarities picked up in this essay can be interpreted, by basing on traditional concepts, except for the number density effect.